Alcohol Exposure Induces Nucleolar Stress and Apoptosis in Mouse Neural Stem Cells and Late-Term Fetal Brain - Yanping Huang; George R. Flentke; Olivia C. Rivera; Nipun Saini; Sandra M. Mooney; Susan M. Smith (Cells, 2024)
Prenatal alcohol exposure (PAE) is a leading cause of neurodevelopmental disability through its induction of neuronal growth dysfunction through incompletely understood mechanisms. Ribosome biogenesis regulates cell cycle progression through p53 and the nucleolar cell stress response. Whether those processes are targeted by alcohol is unknown. Pregnant C57BL/6J mice received 3 g alcohol/kg daily at E8.5–E17.5. Transcriptome sequencing was performed on the E17.5 fetal cortex. Additionally, primary neural stem cells (NSCs) were isolated from the E14.5 cerebral cortex and exposed to alcohol to evaluate nucleolar stress and p53/MDM2 signaling. Alcohol suppressed KEGG pathways involving ribosome biogenesis (rRNA synthesis/processing and ribosomal proteins) and genes that are mechanistic in ribosomopathies (Polr1d, Rpl11; Rpl35; Nhp2); this was accompanied by nucleolar dissolution and p53 stabilization. In primary NSCs, alcohol reduced rRNA synthesis, caused nucleolar loss, suppressed proliferation, stabilized nuclear p53, and caused apoptosis that was prevented by dominant-negative p53 and MDM2 overexpression. Alcohol’s actions were dose-dependent and rapid, and rRNA synthesis was suppressed between 30 and 60 min following alcohol exposure. The alcohol-mediated deficits in ribosomal protein expression were correlated with fetal brain weight reductions. This is the first report describing that pharmacologically relevant alcohol levels suppress ribosome biogenesis, induce nucleolar stress in neuronal populations, and involve the ribosomal/MDM2/p53 pathway to cause growth arrest and apoptosis. This represents a novel mechanism of alcohol-mediated neuronal damage.